Endodormancy Release Can Be Modulated by the GA4-GID1c-DELLA2 Module in Peach Leaf Buds - Li, Sen; Wang, Qingjie; Wen, Binbin; Zhang, Rui; Jing, Xiuli; Xiao, Wei; Chen, Xiude; Tan, Qiuping; Li, Ling (Frontiers in Plant Science, 2021)
Gibberellin (GA) plays a key role in the release of bud dormancy and the GA receptor GID1 (GIBBERELLIN INSENSITIVE DWARF1) and DELLA protein are the GA signaling parts, but the molecular mechanism of GA-GID1-DELLA module regulating leaf bud dormancy in peach (Prunus persica) is still not very clear. In this study, we isolated and characterized the GID1 gene PpGID1c from the peach cultivar “Zhong you No.4.” Overexpressing PpGID1c in Arabidopsis promoted seed germination, which indicated that PpGID1c has an important function in dormancy. The expression level of PpGID1c in peach leaf buds during endodormancy release was higher than that during ecodormancy and was positively correlated with GA4 levels. Our study also found that GA4 had the most obvious effect on promoting the bud break, indicating that GA4 may be the key gibberellin to promoting peach leaf bud endodormancy release. Moreover, a quantitative real-time PCR (qRT-PCR) found that GA4 could increase the expression of the gibberellin signaling gene PpDELLA2. A yeast two-hybrid (Y2H) assay suggested that the PpGID1c interaction with the PpDELLA1 protein was not dependent on gibberellin, while the PpGID1c interaction with PpDELLA2 required GA4 or another gibberellin. These findings suggested that the GA4-GID1c-DELLA2 module regulates peach leaf bud endodormancy release, with this finding significantly enhancing our comprehensive understanding of bud endodormancy release and revealing a new mechanism for regulating leaf bud endodormancy release in peach.